2016
DOI: 10.1080/17425255.2016.1192126
|View full text |Cite
|
Sign up to set email alerts
|

A short-term high fat diet increases exposure to midazolam and omeprazole in healthy subjects

Abstract: Objectives: Knowledge of factors contributing to variation in drug metabolism is of vital importance to optimize drug treatment. This study assesses the effects of a short-term hypercaloric high fat diet on metabolism of five oral drugs, which are each specific for a single P450 isoform: midazolam (CYP3A4), omeprazole (CYP2C19), metoprolol (CYP2D6), S-warfarin (CYP2C9) and caffeine (CYP1A2). Methods: In 9 healthy volunteers, pharmacokinetics of the five drugs were assessed after an overnight fast at two separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…Preclinical studies have found decreased UGT1A1 expression in obese and steatotic rats [33]. Accordingly, in a previous clinical study we found decreased hepatic drug enzyme activity (i.e., CYP3A4 and CYP2C19) after this short-term high-fat diet in healthy subjects [34]. A reason for the current finding could be opposing effects on glucuronidation and on P450 enzyme activity, resulting in a final net lack of effect on acetaminophen exposure.…”
Section: Discussionsupporting
confidence: 54%
“…Preclinical studies have found decreased UGT1A1 expression in obese and steatotic rats [33]. Accordingly, in a previous clinical study we found decreased hepatic drug enzyme activity (i.e., CYP3A4 and CYP2C19) after this short-term high-fat diet in healthy subjects [34]. A reason for the current finding could be opposing effects on glucuronidation and on P450 enzyme activity, resulting in a final net lack of effect on acetaminophen exposure.…”
Section: Discussionsupporting
confidence: 54%
“…Such diets also have selective effects on drug metabolizing enzymes. In a recent study on five different drugs, each metabolized by a different CYP, it was shown that the high fat diet increased exposure to the benzodiazepine sedative midazolam and gastric proton pump inhibitor omeprazole, indicating modulation of CYP3A4 and CYP2C19, respectively [ 43 ]. This is further confirmation of the fact, discussed above, that these two CYPs are targeted by lifestyle changes in metabolism, though the effects of high fat intake appear to differ from those of obesity.…”
Section: Dietmentioning
confidence: 99%
“…[10][11][12] We previously showed that a 3-day, hypercaloric, high-fat diet increased the exposure to oral midazolam (probe for CYP3A4) and omeprazole (probe for CYP2C9) in healthy subjects. 13 Although studies of the effects of hepatic steatosis on phase 1 and phase 2 drug metabolism have shown inconclusive results, the effects on CYP2E1 and CYP3A4 activity exhibit consistent trends. 14 For example, patients with obesity and affected by hepatic steatosis showed increased CYP2E1 activity, which was reduced after weight loss.…”
Section: Introductionmentioning
confidence: 99%